Everyday school violence: an educator's guide to safer schools - Daly, Sarah E. (Rowman & Littlefield, 2018)
"This book provides a comprehensive approach to addressing violence issues using research and evidence-based practices. By offering educators critical ways to measure, and approach violence and prevention, the book provides easy-to-implement suggestions and processes by which educators can created tailored programs to their schools' own needs"--